Body Area Networks: Channel Models and Applications in Wireless Sensor Networks (2011)
Nowadays, wireless Body Area Networks (wBAN) have gained more relevance, in particular in the areas of health care, emergencies, ranging, location, domotics and entertainment applications. Regulations and several wireless protocols and standards have appeared in recent years. Some of them, like Bluetooth, ZigBee, Ultra Wide Band (UWB), ECMA368, WiFi, GPRS and mobile applications offer different kinds of solutions for personal area communications. In this chapter, body area network channel modelling will be described; also, a brief description of the applications and state-of-the-art of regulation and standardization processes pertaining to these kinds of networks will be presented. For each topic, the chapter shows not only the main technical characteristics, but also the technical problems and challenges in recent and future research. Finally, the chapter provides an analysis of Body Area Networks, opinions about the future and possible scenarios in the short- and medium-term for the development of standards and applications and their impacts on our daily lives.